2019
DOI: 10.4103/heartviews.heartviews_4_19
|View full text |Cite
|
Sign up to set email alerts
|

De Winter sign in inferior leads: A rare presentation

Abstract: De Winter pattern in anterior leads has been extensively described. However, there is only one case report of this pattern in inferior leads in English literature. Here, we describe a case of acute inferior wall myocardial infarction with thrombotic right coronary artery occlusion who presented with the classical De Winter sign in inferior leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This pattern accounts for 2% of anterior STEMI cases and it is associated with proximal occlusion of the left anterior descending artery. A similar pattern in inferior leads has rarely been described in literature 2 , 3 . In this patient, the ST elevation in V1-V2 is likely secondary to the right ventricular involvement.…”
Section: Discussionsupporting
confidence: 76%
“…This pattern accounts for 2% of anterior STEMI cases and it is associated with proximal occlusion of the left anterior descending artery. A similar pattern in inferior leads has rarely been described in literature 2 , 3 . In this patient, the ST elevation in V1-V2 is likely secondary to the right ventricular involvement.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 51 out of 86 articles included 83 patients ( Ahmadi, KhamenehBagheri, Vojdanparast, & Jafarzadeh‐Esfehani, 2019; Canakci, Turgay, Acar, & Mert, 2018; Carr, O'Shea, & Hinfey, 2016; Carrington, Santos, Picarra, & De, 2018; Chen, Wang, & Huang, 2020; de Winter, Adams, & Amoroso, 2019; Fiol Sala, Bayés de Luna, Carrillo López, & García‐Niebla, 2015; García‐Izquierdo, Parra‐Esteban, Mirelis, & Fernández‐Lozano, 2018; Giovanni & Francesco, 2020; Goktas, Sogut, Yigit, & Kaplan, 2017; Grandjean, Degrauwe, Tessitore, & Iglesias, 2019; Hanna & Glancy, 2016; He, Liu, & Wang, 2020; Hennings & Fesmire, 2012; Karna, Chourasiya, Chaudhari, Bakrenia, & Patel, 2019; Lam, Cheung, Wai, Wong, & Tse, 2019; Li, Li, Man, Li, & Long, 2019; Lin, Wen, Wu, & Xu, 2019; Mahajan, Batra, & Gupta, 2018; Martínez‐Losas & Fernández‐Jiménez, 2016; Massobrio, Scarrone, & Valbusa, 2016; Montero Cabezas, Karalis, & Schalij, 2016; Montero‐Cabezas, van‐der‐Kley, Karalis, & Schalij, 2015; Niimi, Ooka, Shiraishi, & Fukuda, 2019; Patel, Baker, Paterick, & Tajik, 2017; Pica, Ballestrero, Pistis, & Crimi, 2016; Pranata, Huang, & Damay, 2018; Qayyum, Hemaya, Squires, & Adam, 2018; Qu, Tao, & Liu, 2019; Rao, Wang, & Zhang, 2018; Rodrigues, Gomes, Drumond, & Pereira, 2016; Samadov, Akaslan, Cincin, Tigen, & Sarı, 2014; Sunbul, Erdogan, Yesildag, & Mutlu, 2015; Thabouillot, Bouvier, & Roche, 2017; Tsutsumi & Tsukahara, 2018; Verouden et al., 2009; Viejo‐Moreno, Rubio‐Muñoz, Cabrejas‐Aparicio, & Novo‐García, 2018; Viejo‐Moreno, Rubio‐Muñoz, Cabrejas‐Aparicio, & Novo‐García, 2018; de Winter, Adams, Verouden, & de Winter, 2016; de Winter et al., 2008; Xu, Wang, Liu, & Chen, 2018; Xu, Jiang, & Feng, 2018; Xu, Lu, & Jin, …”
Section: Resultsmentioning
confidence: 99%
“…We excluded 13 patients due to poor ECG quality (de Winter et al., 2019; Viejo‐Moreno et al., 2018; de Winter et al., 2016). The remaining 70 patients included 60 patients (Ahmadi et al., 2019; Canakci et al., 2018; Carr et al., 2016; Carrington et al., 2018; Fiol Sala et al., 2015; Giovanni & Francesco, 2020; Goktas et al., 2017; Grandjean et al., 2019; Hanna & Glancy, 2016; He et al., 2020; Hennings & Fesmire, 2012; Lam et al., 2019; Li et al., 2019; Lin et al., 2019; Mahajan et al., 2018; Martínez‐Losas & Fernández‐Jiménez, 2016; Montero‐Cabezas, van‐der Kley, Karalis, & Schalij, 2015; Niimi et al., 2019; Patel et al., 2017; Pica et al., 2016; Pranata et al., 2018; Qayyum et al., 2018; Qu et al., 2019; Rao et al., 2018; Rodrigues et al., 2016; Samadov et al., 2014; Thabouillot et al., 2017; Verouden et al., 2009; Viejo‐Moreno et al., 2018; de Winter et al., 2008, 2016; Xu, Wang, et al., 2018; Xu, Jiang, et al., 2018; Xu, Lu, et al., 2019; Xu, Xu, et al., 2019; Yang et al., 2017, 2019; Zhang et al., 2019; Zhao et al., 2016; Zorzi et al., 2012), in whom the acute disease process was caused by a lesion in the LAD (LAD group), and 10 patients with another culprit artery or other etiology (non‐LAD group): two patients with first diagonal branch (D1) occlusion (Lin et al., 2019; Montero Cabezas et al., 2016), one with obtuse marginal artery (OM) occlusion (Xu, Zou, et al., 2019), one with microvascular dysfunction (MVD; Chen et al., 2020), two with right coronary artery (RCA) disease (Karna et al., 2019; Tsutsumi & Tsukahara,…”
Section: Resultsmentioning
confidence: 99%
“…Based on a systematic review by Morris and Body, the de Winter pattern has a high positive predictive value (95.2%-100%) for acute occlusion of LAD artery. It can also occur in the right coronary artery and left circumflex artery …”
Section: Discussionmentioning
confidence: 99%
“…It can also occur in the right coronary artery and left circumflex artery. 3,4 CME at jamacmelookup.com Originally, the de Winter pattern was considered a stable condition until reperfusion. 5 However, data obtained in previous studies 6 indicated that this ECG pattern may be a transient ECG phenomenon.…”
Section: Discussionmentioning
confidence: 99%